New Insights Into Mouthings: Evidence From a Corpus-Based Study of Russian Sign Language - Bauer, Anastasia; Kyuseva, Masha (Frontiers in Psychology, 2022)
While some aspects of mouthings have recently been researched, many topics in the use of this cross-modal contact phenomenon in sign languages remain un(der)studied and not much is known about mouthings in Russian Sign Language (RSL). This article examines the use of mouthings as these are used by the native RSL signers. Based on the data from the online RSL Corpus as well as the additional elicited data, we describe the distribution, frequency, functions, and spreading patterns of mouthings in the novel data. The article aims to contribute new insights on the use, function, and origin of mouthings in this sign language. Our findings show that sign languages vary greatly in the use of mouthings. Moreover, we describe mouthings as a lexicalization marker and a written language contact phenomenon. This study has a potential to provide a better understanding of the use of such contact induced feature as mouthings in sign languages in general and reveals a more complex interplay of the modalities of signed, spoken and written languages than previously thought.